Prediction of performance by heart rate-derived parameters in recreational runners. Issue 18 (17th September 2018) - Etxegarai, Urtats; Insunza, Ainhoa; Larruskain, Jon; Santos-Concejero, Jordan; Gil, Susana M; Portillo, Eva; Irazusta, Jon
ABSTRACT: We investigated whether heart rate (HR)-derived parameters are accurate performance predictors in endurance recreational runners. One hundred thirty recreational athletes completed an incremental running test (4´running + 1´rest). After each stage, we recorded HR, % of maximum HR (%HRmax), and blood lactate. We also assessed HR after each recovery period, and calculated lactate and HR recovery thresholds and HR deflection point. We tested these parameters for associations with running performance, as measured by peak treadmill speed (PTS) and personal best International Association of Athletics Federations (IAAF) score. The %HRmax at 14.5 km·h −1 correlated with PTS (r = −0.92), and IAAF score (rho = −0.80). The magnitudes of the correlations of lactate-related parameters with PTS (|r| = 0.84 to 0.86) or IAAF score (|rho| = 0.70 to 0.77) in absolute values were slightly lower. The correlations detected between other HR-derived parameters and running performance were weaker (|r or rho| = 0.24 to 0.70). Regression models identified %HRmax at 14.5 km·h −1 as the strongest predictor of both PTS (β = −0.72) and IAAF score (β = −0.72). Consequently, tests based on %HRmax may provide a non-invasive and inexpensive alternate method for predicting the performance of these athletes.